Conceptualising community engagement through the lens of African indigenous education - Surversperi Suryakumari Rajah (Perspectives in Education, 2020)
The conceptualisation of “community engagement” at Higher Education in South Africa remains a topic for debate in the transformation agenda. South African Indigenous knowledge has been transmitted and perennially refreshed through educational pedagogy that are characterized by a sensitivity to African Philosophy, axiology and the spirit of Ubuntu. This article presents a qualitative critical review from the perspective of African indigenous education of the conceptualisation of community engagement. Community engagement is explored as a contemporary pedagogical counterpart to the indigenous pedagogies that supported African epistemology and axiology and community engagement is positioned within a natural evolution of the South African indigenous education and human development framework. Since children are the most vulnerable and affected community it is postulated that a student-centred framework for community engagement would offer an empowering praxis for a new South African Indigenous Education. Community engagement conceptualised within African Indigenous Knowledge Systems is argued as a means towards authentic transformation giving “voice” and “agency” to communities across all levels of education. Within this framework, the article affirms the use of indigenous concepts and practices within a transformed education system where Higher Education assumes a key role-player in human development from the cradle to the grave.